Further records of the opossum shrimp Neognathophausia ingens (Dorhn, 1870) (Peracarida: Lophogastrida: Gnathophausiidae) from Brazil - Huber, Augusto Frederico; Ribeiro, Felipe Bezerra; de Araujo, Paula Beatriz (Zootaxa, 2019)
Neognathophausia ingens (Dohrn, 1870) is a bathypelagic crustacean distributed worldwide. In the western Atlantic it has been recorded off the La Plata region, Argentina, and off the coast of Brazil, from the state of Bahia to Rio de Janeiro. We provide new records of N. ingens from the state of Rio Grande do Sul, Brazil, about 1188 km south of its previous distribution limit off Brazil, filling the gap between the central West Atlantic and Argentina. Five specimens were analyzed and drawings for all body regions and appendages are presented. Mandible, thoracopods 2, 4, 5, 6 and 8 and pleopods are illustrated and described for the first time. An updated synonym list and a distribution map for this species in Brazil are provided.